2021
DOI: 10.1155/2021/6643884
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Rock Uniaxial Compressive Strength and Deformation Failure Law under Different Size Conditions

Abstract: Rock engineering occupies an important position in the 21st century. In the face of rock engineering disasters, we are only looking for the essential problems through experiments on rocks, but rock experiments cannot be realized in large numbers, so the article uses numerical simulation software RFPA (Realistic Failure Process Analysis) 2D Basic to simulate rock under different size conditions numerically. In this paper, a rock model with a diameter of 50 mm is used for simulation research. Meanwhile, five cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…For example, Xie et al (2021) studied the brittleness and ductility of different rocks (Liang andSong, 2021 andTang et al, 2020). Some scholars conducted numerical simulation analysis on the failure characteristics of rock under unloading rate, and some scholars (Li et al, 2021a andTian et al, 2021) also conducted physical tests and numerical theoretical studies on the failure of rock under various conditions (Gabriel et al, 2021). Qiu et al (2010) analyzed the deformation law of JIN PING deep-buried marble under different confining pressure unloading rates and found that the axial deformation and dilatancy of marble were significantly affected by confining pressure unloading rates.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Xie et al (2021) studied the brittleness and ductility of different rocks (Liang andSong, 2021 andTang et al, 2020). Some scholars conducted numerical simulation analysis on the failure characteristics of rock under unloading rate, and some scholars (Li et al, 2021a andTian et al, 2021) also conducted physical tests and numerical theoretical studies on the failure of rock under various conditions (Gabriel et al, 2021). Qiu et al (2010) analyzed the deformation law of JIN PING deep-buried marble under different confining pressure unloading rates and found that the axial deformation and dilatancy of marble were significantly affected by confining pressure unloading rates.…”
Section: Introductionmentioning
confidence: 99%